Heterogeneous spatiotemporal streamflow response to large-scale climate indexes in the Eastern Alps ... - Ciria, Teresa Perez; Labat, David; Chiogna, Gabriele (Zenodo, 2022)
Analyzing temporal and spatial variability of river discharge and the impacts of large-scale climate oscillations on hydrological systems are of particular interest in Alpine catchments, which have been proved to be especially sensitive to climatic drivers. The impact of climate oscillation indexes may show a delayed response and therefore the correlation between climatic drivers and streamflow is challenging to be properly identified. For this purpose, wavelet transform (WT) is recognized as a suitable tool able to determine the crucial scales of variability. In this work, first we explore the periodicities and the coherence among several climatic indexes: North Atlantic Oscillation Index (NAO), Mediterranean Oscillation Index (MO), Greenland Blocking Index (GB), and Artic Oscillation Index (AO). This analysis shows the complementary information that different oscillation indexes provide and the need to consider their impacts on streamflow simultaneously. Previous work revealed a heterogeneous and complex ...